If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4t + -5) = 0 Reorder the terms: 3(-5 + 4t) = 0 (-5 * 3 + 4t * 3) = 0 (-15 + 12t) = 0 Solving -15 + 12t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 12t = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 12t = 0 + 15 12t = 0 + 15 Combine like terms: 0 + 15 = 15 12t = 15 Divide each side by '12'. t = 1.25 Simplifying t = 1.25
| 2w^2-2w=3w | | 4r^2-1=7r | | x+(x*0.04)=54 | | 3v+9-11v=23 | | x-2y=-6x+1 | | (3x-18)=360 | | 3=7p+8 | | -2r=20-r | | 3x^3+9x^2-18x=0 | | 13q-7q=6 | | 4[x+5(x+7)]=-92 | | 3ln5-3ln3/4ln3-ln5 | | F(x)=3(0.5)-2 | | p-10/-3=-2 | | (4x+2)=(2x+8) | | 3n^2-14n-15=0 | | 7k=5k-20 | | 11=12-7y | | 6x-8=-3x+64 | | (x+5)=4x+5 | | -y^2-4=-y | | 18-7j=-15j-6 | | X-8=4.4 | | 135=10x+10y+xy | | -12+11m=10m | | 12a/4=5 | | 8(4x-5)=11(9+8x) | | -9u+11u=-18 | | Z-10=2 | | 6x+7=28+x+19 | | y=300x+80 | | C+9=9 |